Pequi (Caryocar brasiliense) Waste Extract as a Synergistic Agent in the Microbial and Physicochemical Preservation of Low-Sodium Raw Goat Cheese - Moreira, Rodrigo V.; Vieira, Carla P.; Galvan, Diego; Castro, Vinicius S.; Lima, Rayssa S.; Mutz, Yhan S.; Delgado, Karina F.; Rosario, Anisio Iuri L.; Mano, Sérgio B.; Costa, Marion P.; Conte-Junior, Carlos A. (Frontiers in Nutrition, 2022)
The growth of spoilage and pathogenic bacteria during storage represents significant losses in marketing raw milk cheeses. Thus, reducing NaCl in these products is challenging, as sodium has a critical antimicrobial role. Despite advances in non-thermal technologies, the short shelf life still limits the availability of raw goat cheese. Thus, combined preservation methods can be promising because their synergies can extend shelf life more effectively. In this context, Principal Component Analysis (PCA) was applied to variables to investigate the effect of pequi waste extract (PWE), a native Brazilian fruit, combined with UV-C radiation (CEU) and vacuum packaging (CEV) on the preservation of low-sodium raw goat cheese. CEV samples had lower loadings for Staphylococcus subsp. and Enterobacteriaceae than other treatments in PC2, having a count's reduction up to 3-fold (P < 0.05) compared to vacuum alone. In contrast, CEU showed an increase of up to 1.2-fold on staphylococcal count compared to UV-C alone. Still, the addition of PWE to UV-C-treated cheeses resulted in 8.5 % protein loss. Furthermore, PWE, especially in CEV, delayed post-acidification during storage. It made CEV up to 4.5 and 1.6-fold more stable for color and texture, respectively than vacuum alone. These data strongly suggest that PWE may be a novel and promising synergistic agent in the microbial and physicochemical preservation of low-sodium raw milk cheese when combined with the vacuum.